(untitled) (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: The study aimed to determine the potential anthelmintic activity of the ethyl acetate extract of Eleusine indica that will result in an effective reduction in fecal egg per gram (EPG) counts in naturally infected goats compared to the commercial anthelmintic levamisole. Materials and Methods: The experimental animals were 21 goats naturally infected with gastrointestinal nematodes. The goats were divided into groups that were given a single dose of E. indica extract. Five concentrations of E. indica were tested for anthelmintic activity: 100, 200, 300, 400, and 500 mg extract/kg body weight. Fecal sample collection was done before treatment, during the first treatment, and every week thereafter for 28 days post-treatment (dpt). A modified McMaster technique was used to determine the EPG of feces, and the mean efficacies of the extracts were compared with those of the commercial anthelmintic levamisole. Results: As early as 7 dpt, there was an observed reduction in the epg counts after the administration of E. indica extracts across all concentrations. Administering 500 mg of extract/kg body weight resulted in a maximum efficacy of 56.21%. However, the efficacy achieved was lower than that of levamisole (96.83%). Conclusion: The results show that the E. indica extract can reduce the fecal EPG counts of naturally infected goats, thus creating a potential natural anthelmintic that can be developed further. J. Adv. Vet. Anim. Res., 10(3): 342–346, September 2023 http://doi.org/10.5455/javar.2023.j686